Does e-HRM improve labour productivity? A study of commercial bank workplaces in Pakistan. Issue 2 (12th February 2018) - Iqbal, Naveed; Ahmad, Mansoor; M.C. Allen, Matthew; Raziq, Muhammad Mustafa
Abstract : Purpose: Drawing on data from a unique, large-scale survey, the purpose of this paper is to examine the links between e-HRM and perceived labour productivity both directly and through the mediating role of HR service quality amongst commercial-bank workplaces in Pakistan, many of which have introduced e-HRM. Design/methodology/approach: The authors use partial least squares structural equation modelling to examine the direct links between e-HRM and productivity as well as the mediated links between e-HRM, perceived HR service quality and productivity. Findings: The authors show that e-HRM practices have a statistically significant, positive effect on managers' perceptions of labour productivity. The authors also reveal that e-HRM practices influence the quality of HR service, and that the quality of HR services fully mediates the relationship between e-HRM practices and managers' perceptions of labour productivity. Practical implications: The results highlight the importance of designing and implementing e-HRM systems so that they support organisation workflow and enable workers to carry out a range of HR and non-HR activities more efficiently. In particular, this study suggests that managers should focus on how e-HRM impacts on HR service quality in a holistic way, as this is the "route" via which e-HRM can improve labour productivity. Originality/value: Existing research has demonstrated a link between e-HRM and the quality of HR services; however, these studies downplay the potential impact of e-HRM on labour productivity, a key organisational outcome and one that e-HRM aims to improve. This study contributes to the HRM literature by identifying how e-HRM can improve labour productivity by enhancing the perceived HR service quality. This study, therefore, provides the basis for future theory developments in this area.